Social Security Programs in Islamic Law: A Comparative Study of Fatwa Institutions on Indonesia’s Health Insurance - Sopa Sopa; Rini Fatma Kartika; Nurhadi Nurhadi; Dina Febriani Darmansyah; Taufiqurokhman Taufiqurokhman; Ma’mun Murod (Unissula, 2024)
This research addresses the divergence of scholarly opinions regarding the legal status of Indonesia's National Health Insurance (BPJS Kesehatan) and its implications for Sharia compliance. The controversy arises from varying arguments put forth by the Indonesian Ulema Council (MUI) and Nahdlatul Ulama as the largest Islamic organization in Indonesia, which has implications for the pro-people government program. The study aims to identify and analyze the factors contributing to the disparities in fatwas issued by MUI and NU concerning national health insurance. Additionally, it examines the role of scholars in shaping public policies to ensure their alignment with Sharia principles. The method used in thos study is by employing a descriptive-analytical approach, this research combines document studies and interviews for data collection. Qualitative analysis, guided by ushul fiqh and fiqh siyasa principles, is used to evaluate the controversies surrounding national health insurance issues. The research reveals that discrepancies in fatwa rulings are rooted in differences in the focus of study. MUI emphasizes the contractual aspect, deeming National health insurance incompatible with Sharia principles. In contrast, NU highlights the program's societal benefits, considering it Sharia-compliant due to its social insurance components. This study demonstrates that scholars' involvement in policy formulation is essential to ensure compliance with Islamic law. The divergence of fatwas regarding national health insurance underscores the need for greater scholarly input in shaping pro-people government programs. This research offers a comprehensive analysis of the national health insurance controversy from a scholarly perspective, shedding light on the critical role of scholars in policy-making processes in predominantly Muslim countries